If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1-10y-3=0
We simplify the equation to the form, which is simple to understand
1-10y-3=0
We move all terms containing y to the left and all other terms to the right.
-10y=0-1+3
We simplify left and right side of the equation.
-10y=+2
We divide both sides of the equation by -10 to get y.
y=-0.2
| s=(u-w)/t | | -3x-5y=-39 | | -4x+3y=-23 | | 2x+15y=120 | | 3x-5y=-39 | | 5x+5y=-35 | | x+4/x-2=x+2/x+4 | | 128-9x=7x+16 | | 3(x+2y)-2(3x-y)simplfy= | | 6/x=7/x-3 | | 3x+5y=-36 | | -3-5x=13-10x | | 228-6x=30x+20 | | 5-10x=125-38x | | 4.8x+1=3.8x | | 48x+1=3.8x | | N-33=19 | | -x=4x+3 | | -1(7b-9)=-2 | | 5x+5y=56 | | 1-4(x+2)=7x-29 | | (x+9)=4x+3 | | 5x+5y=51 | | 3(6x-3)=72 | | y=(2x-5)(x^2-6x+8) | | 1-4(x+2)=7x+29 | | 1/6(5X-7)=3 | | 18x-9=72 | | 18x-15=72 | | 3/5(30x-15)=72 | | 1/9x+1=4 | | 6q^3-16q^2+10q=0 |